Rethinking the Indonesia Smart Program (PIP): A Policy Review and Solutions for Better Student Outcomes - Roudoh; Wanada Siti Salsabilah; Aji Wahyudin; Suci Hidayati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The Indonesia Smart Program (PIP), initiated by the government, is a financial assistance scheme targeting students from economically disadvantaged families to ensure equitable access to education. As stipulated in the Ministry of Education and Culture Secretary General Regulation No. 3 of 2021, PIP aims to reduce barriers to education by increasing enrollment rates, providing opportunities for continued schooling, and minimizing dropout rates. By allocating substantial educational subsidies, the program seeks to alleviate financial burdens, enabling students to focus on their education.  This research examines the effectiveness and challenges of PIP implementation, employing William Dunn's public and educational policy analysis framework. The findings highlight that PIP has positively influenced student participation and academic achievement, particularly for underprivileged groups. However, the study identifies critical issues in the distribution process, including potential misuse of funds by schools or parents. To address these concerns, stringent monitoring by schools and committees is essential to ensure funds are used as intended. This study underscores PIP’s role as a strategic policy solution to bridge educational inequalities while calling for enhanced transparency and accountability in its implementation. Recommendations are provided to optimize fund utilization and ensure the program's long-term impact on improving education access and quality.